Why Is the Japanese Supreme Court So Conservative? - Shigenori Matsui (Washington University Law Review, 2011)
The Article explores the development of a conservative constitutional jurisprudence by the Japanese Supreme Court. It describes the process and the power of judicial review in the country. It stresses the reluctance of Japanese judges to consider the Constitution of Japan as a source of positive law to be enforced by the judiciary.
Keywords: Judicial review -- Japan; Constitutional law; Constitutional law -- Japan; Japan. Daishin' in